The Phenomena of Leadership and Consistency in Implementing Quality Management on Vocational High Schools and Their Influence on School Quality - Anggraeni, Nina; Komariah, Aan; Meirawan, Danny; Kurniatun, Taufani C (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the phenomena of leadership and consistency in implementing quality management on vocational high schools and their influence on school quality. The research method used was a quantitative approach. The study population consisted of 28 Vocational High Schools in DKI Jakarta. The data collection technique used was a questionnaire with a total of 240 teachers. For validation, interviews and document analysis were conducted. The results of the study showed the Weighted Mean Score of task oriented leadership was in fair category, consistency in implementing quality assurance was in good categories, and school quality variables was in fair category. Significance value of task oriented leadership and consistency in implementing quality assurance on school quality was in positive direction. The correlation coefficient value was in fair category.